Influence of Membrane Type on Some Electrical Properties of a Single Microbial Fuel Cell - Bouzidi, H.; Otmani, L.; Doufnoune, R.; Zerroual, L.; Benachour, D. (Engineering, Technology & Applied Science Research, 2022)
The effects of different parameters on the electric output of air-cathode microbial fuel cells were investigated in this work. The single microbial fuel cell was equipped by modifying Proton Exchange Membranes (PEM). Two membrane types were prepared: first by using the combination of Poly Vinyl Alcohol (PVA) with Polystyrene Sulfonate (PSSNa), while the second membrane was elaborated by mixing Poly Vinyl Chloride (PVC) with Methyl Tri-Octyl Ammonium (MTOA) chloride. The PEMs were incorporated into the air-cathode to form a Membrane Electrode Assembly (MEA) to promote electricity generation. PVA/PSSNa and PVC-MTOA membranes were synthesized by solution casting method. Fourier Transform Infrared Spectroscopy (FTIR), Ultraviolet (UV) Visible spectroscopy, Scanning Electronique Microscope (SEM), Differential Scanning Calorimetry (DSC), and water Contact Angle (CA) were used as characterization techniques to explore the membrane structure and properties. The performance and the electric capacity of the microbial fuel cell in real time were operated using an external resistance of 5kΩ. Impedance and resistance capacity were determined using the polarization method. It was found that the internal resistance of the PVA/PSSNa and PVC-MTOA membranes were 50 and 350Ω respectively. The voltage values at open circuit of the cells using PVA/PSSNa and PVC-MTOA membranes were 600mV and 150mV respectively. The values of power, current, and power density, are quite interesting. Cells with PVA/PSSNa and PVC-MTOA membranes gave values of 18.24 and 9.64mW.cm-2 respectively.